Literature Review: Relationship of Environmental Risk Factors and the Incidence of Leptospirosis in Settlements (2018–2023) - Nafiah Farisan Nuha; Nuur Anisa Aprilianintyas; Dian Novitasari (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Leptospirosis is zoonotic disease that transmits via natural transmission from vertebrate animals to human beings and vice versa. This disease is caused by an infection of the Leptospira sp. bacterium. It is estimated that there are 1 million cases of Leptospirosis that attack humans worldwide with 60 thousand deaths per year. In Indonesia, such cases and death rates have fluctuated. In 2021, there was a decrease in cases, but the CFR rate increased from 9.1% to 11.4%. Leptospirosis cases become endemic in many countries, especially in tropical and subtropical areas with high rainfall, especially in settlements with poor environmental conditions. Based on previous research, there were differences in the results between several research variables with the incidence of Leptospirosis. This gap underlies the writing of this article to bring together the existing results. Discussion: This study used literature review method for research articles on biotic and abiotic environmental risk factors with Leptospirosis in settlements sourced from scientific publication websites. After going through these stages, 14 final full text articles were obtained. The data used were research studies conducted from January 2018 to April 2023. The articles found show that environmental factors are closely related to the incidence of Leptospirosis in settlements. Conclusion: The variable abiotic environment factors associated with the occurrence of Leptospirosis are temperature, pH, the presence of sewers and puddles. The presence of rats and the presence of animals or livestock are related to biotic environmental factors.